THE EFFECTIVINESS OF KANGAROO MOTHER CARE ON BODY TEMPERATURE STABILITY OF LOW BIRTH WEIGHT INFANTS AT THE PERINATOLOGY ROOM DR. ACHMAD MOCHTAR HOSPITAL BUKITTINGGI - weni lidya hendayani (HUMAN CARE JOURNAL, 2019)
Low Birth Weight (LBW) is a baby with a birth weight less than 2500 grams regardless of gestation. The one of complication  is body temperature instability, and to maintain it, the infants are exposed to the Kangaroo Mother Care (KMC) Method. Data WHO and UNICEF in 2013 with 22 million baby birth in the world, where 16 % birth with low birth weight infants. The purpose of this study was to determine the effect of implementation kangaroo mother care on body temperature stability of low birth weight infants at the perinatology room Dr.Achmad Mochtar Hospital Bukittinggi. This research is a Pre-Eksperimental with one-group pretest-postest design in Agust 2018 as many 15 respondents with accidental sampling technique. The statistical test used is dependent T-test. The result of statistical test show a significant influence between body temperature stability before and after implementation kangaroo mother care with p-value = 0,000 (α ≤ 0.05). So it can be concluded that there is a relationship of The Effectiviness kangaroo mother care on body temperature stability of low birth weight infants. Suggestions to hospital can implementation kangaroo mother care because this method an effective, simple, and cheap method to care low birth weight infant.Kata Kunci   : Kangaroo Mother Care, Body Temperature